2018
DOI: 10.1080/14724049.2018.1502248
|View full text |Cite
|
Sign up to set email alerts
|

Governance and local participation in ecotourism: community-level ecotourism stakeholders in Chiang Rai province, Thailand

Abstract: This paper takes as its starting point the assertion that community-based ecotourism is an activity in which not all members of a community are able to be involved (through barriers or factors of exclusion) and/or wish to be involved (through personal choice). This has implications for discussions about community-level stakeholders, governance and tourism development. Firstly, the paper explores the actors' interactions as they relate to the use of resources and environment. Within this theme are seen more spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 25 publications
1
18
0
4
Order By: Relevance
“…Peran pendam ping desa dalam penyelenggaraan pemerintahan desa sangatlah penting, terutama dalam hal penggalian, penampungan, dan penyaluran aspirasi masyarakat sebagai bentuk parti sipasi pembangunan lingkungan pedesaan serta meningkatkan kinerja dalam mewujud kan keberdayaan masyarakat. Pada akhir nya hal ini dapat menjadi tumpuan harapan masyarakat terhadap pemerintah, terutama programprogram yang diagendakan oleh pemerintah untuk mewujudkan kemandi rian serta kesejahteraan masyarakat desa serta pembangunan di desa yang berkelan jutan (Balázs & Hoffman, 2017;Palmer & Chuamuangphan, 2018;Wang & Li, 2018). Namun, permasalahan pada faktanya, kom petensi pendamping desa masih minim ter utama dalam hal membantu desa dalam pe ngelolaan dananya (Klick, 2016;Sun, Lin, & Chan, 2017;Suresh, 2017).…”
unclassified
“…Peran pendam ping desa dalam penyelenggaraan pemerintahan desa sangatlah penting, terutama dalam hal penggalian, penampungan, dan penyaluran aspirasi masyarakat sebagai bentuk parti sipasi pembangunan lingkungan pedesaan serta meningkatkan kinerja dalam mewujud kan keberdayaan masyarakat. Pada akhir nya hal ini dapat menjadi tumpuan harapan masyarakat terhadap pemerintah, terutama programprogram yang diagendakan oleh pemerintah untuk mewujudkan kemandi rian serta kesejahteraan masyarakat desa serta pembangunan di desa yang berkelan jutan (Balázs & Hoffman, 2017;Palmer & Chuamuangphan, 2018;Wang & Li, 2018). Namun, permasalahan pada faktanya, kom petensi pendamping desa masih minim ter utama dalam hal membantu desa dalam pe ngelolaan dananya (Klick, 2016;Sun, Lin, & Chan, 2017;Suresh, 2017).…”
unclassified
“…For instance, a case study from The Doi Tung Development Project in Thailand shows that when there is conflict of interest, it is difficult for locals to negotiate with authorities because they fear the authority's power (Theerapappisit, 2009). This cultural issue can be observed throughout Thailand and other developing countries such as Cambodia and Indonesia (Cole, 2006;Ellis and Sheridan, 2015;Palmer and Chuamuangphan, 2018). More discussions regarding implementation problems of top-down and bottom-up approach can be seen in Leksakundilok and Hirsch (2008) and Theerapappisit (2009).…”
Section: Discussionmentioning
confidence: 99%
“…Bramwell and Lane (2013) have shown that the level of community participation is determined by social order, social coordination and social practices. In a hierarchical society like Thailand, participation in tourism management is restrictive and exclusive (Palmer & Chuamuangphan, 2018). For tourist routes to be a success there should be an equal opportunities approach to involvement in heritage site management.…”
Section: Discussionmentioning
confidence: 99%